Transferring Halal knowledge and consumerism to the Orang Asli community - Othman, Khadijah; Ramli, Noriah; Hashim, Yumi Zuhanis Has-Yun (Knowledge Transfer Programme, Ministry of Higher Education, Malaysia, 2016)
Industrial Master Plan (IMP) 2006-2020 aimed to make Malaysia a global halal hub for the production and trade in halal goods and services. In order to reach this vision, all the information and output must be channelled throughout all segments of people, including the underserved community such as the Orange Asli community. This Knowledge Transfer Program (KTP) series of projects aimed to create awareness and transfer knowledge on the importance of halal, halal consumerism and skills on slaughtering to the Orang Asli community. The program was conducted under the purview of the IIUM International Institute for Halal Research and Training (INHART) between March 2013 to June 2015 in four selected sites in the state of Pahang, Negeri Sembilan, Selangor and Perak. More than 1000 participants were involved. We have found that the level of halal awareness in the Orang Asli community is minimal with factors related include geographical and educational background as well as language barrier. In conclusion, Orang Asli are an integral part of the Malaysian community. Necessary steps and more concerted efforts must be taken during the early ages of childhood to ensure the chain of halal knowledge would be continuous and sustainable throughout generations.